Dissecting the Regulation of Arachidonic Acid Metabolites by Uncaria rhynchophylla (Miq). Miq. in Spontaneously Hypertensive Rats and the Predictive Target sEH in the Anti-Hypertensive Effect Based on Metabolomics and Molecular Docking - Gao, Lei; Kong, Xinqin; Wu, Wenyong; Feng, Zijin; Zhi, Haijuan; Zhang, Zijia; Long, Huali; Lei, Min; Hou, Jinjun; Wu, Wanying; Guo, De-an (Frontiers in Pharmacology, 2022)
Uncaria rhynchophylla (Miq). Miq. (UR), as a traditional Chinese medicine, was employed in treating hypertension as a safe and effective therapy. The pharmacological properties of UR have characteristics of multiple biological targets and multiple functional pathways. Hypertension is related to impaired metabolic homeostasis and is especially associated with the abnormal regulation of arachidonic acid metabolites, the classical cardiovascular active compounds. This study aimed to examine the anti-hypertensive effect of UR extract (URE) and its regulating role in differential metabolic pathways. The results showed that daily administration of URE at a dose of 4 g crude drug/kg orally could exert hypotensive effects on spontaneously hypertensive rats (SHRs) for eight weeks. Non-targeted metabolomics analysis of the plasma samples suggested that the anti-hypertension effect of URE in SHRs was associated with the reorganization of the perturbed metabolic network, such as the pathways of glycerophospholipid metabolism, linoleic acid metabolism, and arachidonic acid metabolism. For the targeted metabolomics, twenty-eight arachidonic acid metabolites in SHRs were quantitatively analyzed for the first time based on ultra-high performance liquid chromatography-tandem mass spectrometry method after URE administration. URE restored the functions of these cardiovascular active compounds and rebalanced the dynamics of arachidonic acid metabolic flux. Among them, the inhibition of soluble epoxide hydrolase (sEH) enzyme activity and up-regulation of vasodilators epoxyeicosatrienoic acids (EETs) were identified as contributors to the anti-hypertension effect of URE on SHRs, and sEH represented an attractive and promising drug-binding target of URE. With the molecular docking approach, 13 potential anti-hypertension ingredients as well as sEH inhibitors were discovered, which were worthy of further investigation and verification in future studies.